Influence of geographical accessibility to specialist and primary care givers on excess mortality of multiple sclerosis patients in France - Sarah Wilson (BMC Neurology, 2025)
Abstract Background Access to healthcare and socioeconomic deprivation are intricately linked. No studies have been led to measure the effect of healthcare accessibility on mortality in patients with MS so far. The objective was to examine the influence of travel time to the expert MS centre and of the accessibility to primary healthcare services on excess mortality in MS. Methods A retrospective observational cohort study recruited patients from 18 French MS expert centres, with an onset of MS between 1960 and 2015 and a follow-up of up to 30 years. Primary health facility accessibility was measured by the Spatial aCcessibility multiscAlar index. Specialist care accessibility was measured by road travel time to the expert MS centre. Excess death rates (EDR) and excess hazard ratios were studied using additive excess hazard models with multidimensional penalised splines. Results The study included 33,697 patients. Patients with relapsing-onset MS (R-MS) with a travel time of 40 min had the lowest EDR (Men: 1.2 deaths per 100 person-years (95%CI [0.8;1.8]), women: 0.8 deaths per 100 person-years 95%CI[0.6;1.2]), lower than patients who lived further from the centre. No effect of primary care access was found for patients with R-MS, and no effect of accessibility to primary or specialised care was found for patients with primary progressive MS. Conclusion This study reveals the impact of travel time to neurologists on excess mortality in patients with R-MS in France. This distance bias association highlights the importance of preventing a potential selection of patients followed in MS expert centres.